2021
DOI: 10.1080/1369183x.2020.1866515
|View full text |Cite
|
Sign up to set email alerts
|

Cleaners and labourers on Facebook? Bulgarians in the UK between free movers and a digital diaspora

Abstract: This study explores the way Bulgarians living in the UK interact online. We rely on an online survey of attitudes among Bulgarians in the UK, participant observation in Bulgarian support networks during the period 2016-20, as well as qualitative interaction analysis (adapted for non-visual environments) over the course of six months (2019-20) of top posts from the largest online support groups. Our findings point to the gradual consolidation of organised informal support among Bulgarians, especially and predom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The experience of the Malagasy migrants in France is, however, quite different from the solidarity chains of other migrant communities from low-income countries in high-income countries, such as the Bulgarians in the United Kingdom or the dynamics of some African diasporas in the US (Mesbah and Cooper 2019). In fact, if we compare the Facebook groups and pages of the Malagasy migrants in France with those of Bulgarians in the UK, we notice (i) that the Malagasy in France have no specific group or page dedicated to professional exchanges, and (ii) that posts related to this topic in general groups are less frequent than within the Facebook groups and pages of Bulgarians in the UK, as reported by Nancheva (2021). Overall, we believe that this is intimately related to the high level of integration of the Malagasy in France and to their high educational qualifications, as described by Razafindrakoto et al (2017).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The experience of the Malagasy migrants in France is, however, quite different from the solidarity chains of other migrant communities from low-income countries in high-income countries, such as the Bulgarians in the United Kingdom or the dynamics of some African diasporas in the US (Mesbah and Cooper 2019). In fact, if we compare the Facebook groups and pages of the Malagasy migrants in France with those of Bulgarians in the UK, we notice (i) that the Malagasy in France have no specific group or page dedicated to professional exchanges, and (ii) that posts related to this topic in general groups are less frequent than within the Facebook groups and pages of Bulgarians in the UK, as reported by Nancheva (2021). Overall, we believe that this is intimately related to the high level of integration of the Malagasy in France and to their high educational qualifications, as described by Razafindrakoto et al (2017).…”
Section: Discussionmentioning
confidence: 57%
“…1) compared to offline observations. Finally, this choice was motivated by the proven relevance of this platform, since other empirical studies of other diaspora communities in the same line have already been successfully carried out on Facebook (Nancheva 2021;Mesbah and Cooper 2019).…”
Section: Methodsmentioning
confidence: 99%
“…At the same time, research has also shown that online communities enable migrants to connect and ‘glue’ together not only in the virtual space but also in places and localities in which they have come to live (Nancheva, 2021; Oosterbaan, 2010; Sabido, 2017). These studies have demonstrated how online communities facilitate migrant settlement and emplacement in the country of destination, thus providing an important avenue of integration and empowerment especially for more marginalised migrant individuals (Kok and Rogers, 2017; Nancheva, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, research has also shown that online communities enable migrants to connect and ‘glue’ together not only in the virtual space but also in places and localities in which they have come to live (Nancheva, 2021; Oosterbaan, 2010; Sabido, 2017). These studies have demonstrated how online communities facilitate migrant settlement and emplacement in the country of destination, thus providing an important avenue of integration and empowerment especially for more marginalised migrant individuals (Kok and Rogers, 2017; Nancheva, 2021). Scholars have also highlighted the importance of social capital generated by migrants’ online groups, pointing to different ways in which these groups function as informal support networks for their members (Bucholtz and Sūna, 2019; Chen and Choi, 2011; Oh, 2016; Oosterbaan, 2010; Sabido 2017; Nancheva, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation